When God is the Problem: From Allegation to Apologia in the Psalms - Pemberton, Glenn (Stone-Campbell journal, 2014)
Eight psalms of lament accuse God of indefensible behavior, make no confession of culpability for his actions, and offer no expression of trust or praise. Yet rather than moving the reader away from God, these psalms actually provide a path back toward him and demonstrate the possibility of relationship with God despite difficult circumstances.